Ecological basis of extinction risk in birds: Habitat loss versus human persecution and introduced predators - Owens, Ian P. F. (The National Academy of Sciences, 2000)
Understanding the ecological mechanisms that underlie extinction is fundamental to conservation. It is well established that not all taxa are equally vulnerable to extinction, but the reasons for these differences are poorly understood. This may be, in part, because different taxa are threatened by different mechanisms. Theoretically, sources of extinction risk that perturb the balance between fecundity and longevity, such as human persecution and introduced predators, should be particularly hazardous for taxa that have slow rates of population growth. In contrast, sources of extinction risk that reduce niche availability, such as habitat loss, should represent a particular threat to taxa that are ecologically specialized. Here we test these predictions by using a phylogenetic comparative method and a database on 95 families of birds. As theory predicts, extinction risk incurred through persecution and introduced predators is associated with large body size and long generation time but is not associated with degree of specialization, whereas extinction risk incurred through habitat loss is associated with habitat specialization and small body size but not with generation time. These results demonstrate the importance of considering separately the multiple mechanisms that underlie contemporary patterns of extinction. They also reveal why it has previously proven so difficult to identify simple ecological correlates of overall extinction risk.